GEOLOGICAL AND HYDROGEOLOGICAL STUDIES OF MOUNT KLABAT GEOTHERMAL AREA, NORTH SULAWESI - Ivan, Albertus
Mount Klabat is a Quarternary, or 200,000 years old precisely, type B stratovolcano located in North Sulawesi. In general, a Quarternary volcano like this will produce a geothermal system as indicated by the appearance of thermal manifestations on the surface. However, there are no thermal manifestations that appears around Mount Klabat and only cold springs appears. This research aims to understand the geological and hydrogeological conditions in estimating the causes of the absence of thermal manifestations around Mount Klabat, while the purpose of this research is to identify the buried geological structure, estimate the thickness of the impermeable eruption products, and estimate the presence of coldwater aquifers around Mount Klabat that may be related to the phenomenon of the absence of active thermal manifestations here. The method used in this research consist of soil CO2 – Hg and gravity data, geological mapping, and water geochemistry analysis. The result of soil CO2 – Hg and gravity data analysis are pre-field geological structure map. The result of this analysis will be supported by the result of drainage pattern and slope analysis and also validated by geological mapping. Geological structures that are indicated from secondary data analysis but show no indication or evidence on the surface are thought to be buried. The result of geological mapping is a geological map and geological cross sections which are used to estimate the Mount Klabat’s impermeable lithology thickness. The result of water geochemistry analysis is a cold springs anomaly map. These anomalies are thought to occur due to the mixing of thermal fluid from Mount Klabat with the cold water aquifers beneath the surface. The results of all these analyzes are integrated and described in the form of a conceptual model. The result of this research shows that there are faults that interpreted to penetrate into the reservoir so that the reservoir fluid rises to the surface through these faults, but near the surface, these faults are buried by younger eruption products, so the fluid does not appear as a thermal manifestation on the surface. Impermeable lithology in the form of andesite rocks with a thickness of >1000 m prevents the reservoir fluid from emerging to the surface, so the fluid flows into cold water aquifers beneath the surface. The presence of cold water aquifers in the form of pyroclastic breccia, pumice breccia, and ignimbrite at a depth of ±5 m beneath the surface mask the appearance of thermal manifestations on the surface so that the manifestations found on the surface are an anomaly cold springs.